Gymnopus wutaishanensis (Omphalotaceae, Agaricales) a new species from North China - Mao, Ning; Liu, Hong; Fan, Li (Phytotaxa, 2022)
Gymnopus wutaishanensis sp. nov. is described and illustrated from north China. Our molecular phylogenetic analyses based on ITS and LSU sequences supported the establishment of the new species and positioned it in Gymnopus sect. Impudicae. Morphologically, this new species is diagnosed by the combination of basidiomata with tangy and unpleasant odor when fresh, pale orange to pinkish brown pileus, white and relatively dense lamellae, hairy stipes and small basidiospores of (4–)5–6(–7) × (2–)2.5–4 μm.